2015
DOI: 10.18805/ijar.5707
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of sire evaluation methods by using phase and stayablity traits to improve milk yield of Murrah buffaloes

Abstract: The present investigation was conducted on records of 345 Murrah buffaloes maintained at Buffalo Research Centre (BRC), Hisar distributed over 20 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) to compare progeny of 61 sires. Three sire evaluation procedures [ordinary least squares (OLS), regressed least squares (RLS), and best linear unbiased prediction (BLUP)] based on estimated breeding value of phase traits such as ascending pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
2
1
Order By: Relevance
“…Lower ranges for FLMY (553.86) and higher ranges for MY/FLL (1.87) and MY/FCI (2.14) in Holstein Friesian crossbred cattle were reported [8]. The higher range of estimated breeding values of sires by BLUP method for MYLL, MYFCI and MYASC as 5.4 to 7.44, 3.13 to 5.49 and 0.86 to 1.31 in Murrah buffaloes compared to the present study [9].…”
Section: Resultscontrasting
confidence: 51%
“…Lower ranges for FLMY (553.86) and higher ranges for MY/FLL (1.87) and MY/FCI (2.14) in Holstein Friesian crossbred cattle were reported [8]. The higher range of estimated breeding values of sires by BLUP method for MYLL, MYFCI and MYASC as 5.4 to 7.44, 3.13 to 5.49 and 0.86 to 1.31 in Murrah buffaloes compared to the present study [9].…”
Section: Resultscontrasting
confidence: 51%
“…Similar findings were also reported by various researchers; Gaur et al, (2001), Dhaka et al, (2004), Banik and Gandhi (2006), Bajetha (2006), Mukherjee et al, (2007), Kumar et al, (2008), Moges et al, (2009 and Kamaldeep et al, (2015). Rank and product moment correlations among sire merit calculated by various sire evaluation procedures for different performance traits revealed that product moment correlations were comparatively higher than those of rank correlations barring few exceptions.…”
Section: Rank and Product-moment Correlationssupporting
confidence: 87%
“…To improve the efficiency and accuracy of sire evaluation programmes many sire indices has been developed such as by using the procedures of Least-squares (LS), Regressed Least-Squares (RLS), Best Linear Unbiased Prediction (BLUP) and Derivative Free Restricted Maximum Likelihood Method (DFREML). The literature is dotted with conflicting reports (Pundir et al, 2004;Dhaka et al, 2004;Banik and Gandhi, 2006;Raja, 2010;Kamaldeep et al, 2015) on comparative evaluation of various sire evaluation techniques in dairy animals. Therefore, an effort has been made to estimate breeding values for various performance traits by different procedures and comparison of these procedures to find out the most suitable for evaluation of Murrah sires.…”
Section: Introductionmentioning
confidence: 99%
“…The BLUP method was second efficient followed by LSM and SRLS method. Kamaldeep et al, (2015) conducted studies to compare progeny of 61 sires. Three sire evaluation procedures [ordinary least squares (OLS), regressed least squares (RLS), and best linear unbiased prediction (BLUP)] based on estimated breeding value of phase traits such as ascending phase milk yield (APY), peak phase milk yield (PPY),descending phase milk yield (DPY)and stayablity trait such as stayablity life (STAYAB) in Murrah buffalo.…”
Section: Comparison Of Different Sire Evaluation Methodsmentioning
confidence: 99%